Advances in Viroid-Host Interactions - Navarro, Beatriz; Flores, Ricardo; Di Serio, Francesco (Annual review of virology, 2021)
Viroids are small, single-stranded, circular RNAs infecting plants. Composed of only a few hundred nucleotides and being unable to code for proteins, viroids represent the lowest level of complexity for an infectious agent, even below that of the smallest known viruses. Despite the relatively small size, viroids contain RNA structural elements embracing all the information needed to interact with host factors involved in their infectious cycle, thus providing models for studying structure-function relationships of RNA. Viroids are specifically targeted to nuclei (family ) or chloroplasts (family ), where replication based on rolling-circle mechanisms takes place. They move locally and systemically through plasmodesmata and phloem, respectively, and may elicit symptoms in the infected host, with pathogenic pathways linked to RNA silencing and other plant defense responses. In this review, recent advances in the dissection of the complex interplay between viroids and plants are presented, highlighting knowledge gaps and perspectives for future research.